Strahlende Geiselhaft. Jelineks Lärmblendung «Kein Licht»: [Splendid Captivity. Jelinek’s Noise Blinding «No Light»] (Studia austriaca, 2018)
In tracing the function of sound in Elfriede Jelinek’s multi-lingual «Kein Licht» (2011) the article argues that she uses the concept of entropy – the tendency of closed systems to move towards disorder – to depict critically the events of the Fukushima nuclear disaster. Within the realm of death by radiation a polyphony of voices and intertextual references reaching from Sophocles to Thomas Pynchon produce a “blinding by noise”  through which the text turns into an «opera aperta» evoking Umberto Eco’s aesthetic concept and the central role assigned to entropy.